(untitled) (Research, Society and Development, 2023)
Considering the importance of scientific knowledge as a basis for improvement, the gynecology and obstetrics service of Hospital das Clínicas Samuel Libânio considered it necessary to evaluate its health services to seek improvements for its users. For this, the Escala da Qualidade de Serviços de Saúde/Escola Paulista de Medicina (EQSS/EPM) was used, a validated instrument, translated into Portuguese and adapted to the social and cultural context of Brazil. The questionnaire was applied to 50 postpartum women who met the inclusion criteria. The instrument contains 73 statements rated from 1 to 7 that range from “completely disagree” to “completely agree”. The average cutoff considered satisfactory was established at 80%. The questions are divided into items relating to the quality of services offered; user satisfaction; the quality of interpersonal relationships; technical and environmental quality, among others. Out of the 16 groups of items, the one that received the highest score was the one related to “qualification”. The group with the lowest score was the group referring to “relationship”. Therefore, from the perspective of the proposed methodology, the HCSL maternity service received high ratings from its users in all survey questions, except for the relationship between the service team and its users. These data corroborate trends often observed in health services, which increasingly value technical and scientific advances, to the detriment of valuing human relationships and care for the person, and not just the disease.